PENGARUH STRATEGI PENGELOLAAN KELAS TERHADAP KARAKTER DISIPLIN SISWA KELAS II DALAM PEMBELAJARAN MATEMATIKA DI SD NEGERI SUWATU 1 TANON TAHUN PELAJARAN 2025/2026 - Karisma Bhekti Rahayu; Ema Butsi Prihastari; Dite Hastini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of classroom management strategies on the disciplinary character of second-grade students in mathematics instruction at SD Negeri Suwatu 1 Tanon during the 2025/2026 academic year. It is motivated by the persistence of undisciplined behavior during lessons, such as inattentiveness to teacher explanations, inconsistent compliance with classroom rules, and delays in completing assignments. A quantitative approach with a survey method was employed. The research subjects were all 27 second-grade students of SD Negeri Suwatu 1 Tanon, selected as the sample through saturated sampling. Data collection techniques comprised observation, questionnaires, and documentation. The main instrument was a Likert-scale questionnaire tested for validity and reliability, yielding a Cronbach's Alpha coefficient of 0.987, categorized as highly reliable. Data analysis involved classical assumption testing, simple linear regression, a t-test, and the coefficient of determination, using IBM SPSS Statistics 25. The findings reveal that classroom management strategies exert a positive and significant effect on students' disciplinary character, with a coefficient of determination (R Square) of 0.881, indicating that classroom management strategies account for 88.1% of the variance in students' disciplinary character. The better the classroom management strategies implemented by teachers, the higher the disciplinary character exhibited by students during mathematics instruction. This study concludes that classroom management strategy is the primary determinant in shaping the discipline of primary school students, offering practical implications for teachers in designing orderly and conducive mathematics instruction.